Transformational leadership, work motivation and performance: An exploratory study on the context and process / Ong Pooi Fong and Elden Kam Weng Cheong - Ong, Pooi Fong; Kam, Elden Weng Cheong (Research Management Institute (RMI), 2015)
Leadership skills have become an important asset for many organisations as they strive to manage the people that make up the organisations. However, in todays competitive business environment, basic leadership qualities may not be sufficient to sustain the growth of the organisations. This exploratory study aims to look at the influence transformational leaders have on work motivation and performance. The study adopts a qualitative approach using in-depth interviews to solicit corporate and youth leaders' perspectives on successful leadership qualities and challenges, work motivation and performance. Findings revealed that transformational leadership traits are effective in cultivating motivation and higher performance in organisations. An evolving conceptual framework depicting the relationships between leadership, motivation and performance is proposed.